Euphemism in the Reporting of Immoral Acts in Online Media (A Linguistic Review) - Nurul Fadhilah; Raden Khaeru Ahmadi; Yuni Putri Utami (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
In journalism, the role of language is paramount due to its crucial influence on readers. This study aims to identify linguistic units in online media reporting that serve as euphemisms. This research is important because, in the digital age, the ease of accessing news must align with its acceptability and safety for readers. This study employs a descriptive qualitative method with a sociolinguistic approach. The forms of euphemism that appear in reporting on immoral acts in online media include foreign word euphemisms, loan word euphemisms, periphrasis, metaphorical euphemisms, figurative euphemisms, euphemisms used to replace another term, acronym euphemisms, and abbreviation euphemisms. in addition to following the code of ethics, journalists must also understand how to use euphemisms to produce acceptable writing without causing new societal conflicts.